Robot assisted knee joint RoM exercise: A PID parallel compensator architecture through impedance estimation - Akhtaruzzaman, Md.; Shafie, Amir Akramin; Khan, Md. Raisuddin (KeAi Communications Co., 2024)
Knee joint rehabilitation exercise refers to a therapeutic procedure of a patient having dysfunctions in certain abilities to move knee joint due to some medical conditions like trauma or paralysis. The exercise is basically a series of repeated assistive physical movements within the range of motion (RoM) of the joint. Reflex action of limbs during RoM exercise causes inappropriate balance of load which may cause secondary injuries, such as damages of muscle or tendon tissues. Establishing correlation between impedance data and limb motions is important to solve this problem.